Avaliação do processo ensino-aprendizagem no Projeto Podcast “Engenharia de quê?” - Lima, Morgana Timbó (2024)
Teaching in higher education brings together characteristics specific to its audience and its specific field of activity, presenting challenging points that correspond to this identity (Veiga; Fernandes, 2021). The engineering disciplines, included in this group, have adversities observed at national level, considered in the design of the update of the national curricular guidelines for these courses (CNE/CES No. 2/2019) (Brasil, 2019), in order to combat the evasion presented (Carvalho et al., 2017). The extension project ‘Engenharia de Quê?’ was conceived during the health emergency caused by the new coronavirus, SARS-CoV-2, by a lecturer on the Food Engineering course at the Universidade Federal do Ceará, in order to safeguard training quality and dialogue with students in the field, even in an adverse context. This research investigates the pedagogical characteristics of the podcast project, based on the meaning observed by the participants in the context. To this end, the general objective was to ‘Evaluate the pedagogical principles of the “Engenharia de Quê??” extension project linked to the Food Engineering course at the Federal University of Ceará, observing the place of learning assessment in the proposal in the relationship between extension and teaching’. In order to circumscribe the project, the following specific objectives were defined: ‘Identify which theories of learning and assessment touch on what is experienced in the extension project under study, based on the description of the data observed‘, “Unveil what significance the participants attribute to the project as a professional training proposal” and “Map the progress of the project's objectives and relate them to the students” perceptions’. The methodological procedures listed for the fulfilment of the objectives, implemented from 2022 to 2024, consider the Phenomenological Reduction approach (Heidegger, 1986) for data collection and analysis, thus contemplating the meaning constructed by the project members, the research subjects. Bibliographic and documentary research to help understand the results obtained, considered authors from the field of education, such as Bloom (et al., 1972; 1973), Pimenta and Anastasiou (2002), Vygotsky (1991; 1994) and Tardif (2002), and curricular documents that guide pedagogical practice, in order to present the situational context where the subject is inserted (Brasil, 2019). From the research, it can be seen that the discourse of the representation, congregated in units of meaning, is centred on valuing the diversity of learning objectives, of multiple natures and, consequently, the possibility of deepening, made possible in the practices of the podcast context and anticipate ways in which this could be experienced more broadly in the curriculum indicating their own experiences.